2017
DOI: 10.1002/app.44885
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and structural regulation of PLLA porous microspheres via phase inversion emulsion and thermally induced phase separation techniques

Abstract: In this work, a facile, scalable technique was developed to produce biodegradable porous microspheres by combining an oil‐in‐oil (O/O) surfactant‐free phase inversion emulsion technique with thermally induced phase separation (TIPS) method. The effects of PLLA concentration, stirring speed, macromolecule weight, and organic solvents on the size and microstructure of microspheres were investigated by scanning electron microscopy (SEM). The results revealed a highly porous structured microsphere with controllabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Furthermore, this study demonstrates that the addition of mid-solvent may expand selection of controlling factor for pore and skeletal size. For over decades, TIPS with binary good/poor solvent have been widely used, [9][10][11][17][18][19] while this oen limits the condition of fabrication. For example, Tanaka et al reported that PLLA monoliths were produced by TIPS using binary 1,4dioxane/water solvent with the limited ratio around 87/13 w/ w% at 10 wt% of PLLA concentration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, this study demonstrates that the addition of mid-solvent may expand selection of controlling factor for pore and skeletal size. For over decades, TIPS with binary good/poor solvent have been widely used, [9][10][11][17][18][19] while this oen limits the condition of fabrication. For example, Tanaka et al reported that PLLA monoliths were produced by TIPS using binary 1,4dioxane/water solvent with the limited ratio around 87/13 w/ w% at 10 wt% of PLLA concentration.…”
Section: Resultsmentioning
confidence: 99%
“…Among those techniques of producing PLA monoliths, recently, phase separation has been utilized due to its excellent versatility, simplicity, and controllability in pore size compared to other methods. [9][10][11][15][16][17][18][19] Furthermore, good processability is also key factor of this method since the shape of monolith is dependent on the shape of vessels where the phase separation and gelation take place. This method can mainly be classied into two for preparation of monoliths from PLA by types of trigger to occur phase separation: non-solvent induced phase separation (NIPS) and thermally induced phase separation (TIPS).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the polymer solution TIPS process, the polymers are dissolved in the solvent at high temperature, and polymeric particles are generated by the polymer precipitating with cooling . Nie et al . developed biodegradable porous microspheres by the TIPS method.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, they are used as small building blocks in the construction of large organs in bottom‐up tissue engineering . Many research groups have demonstrated the fabrication of porous microbeads using numerous techniques including gas formation, melt‐molding and particle leaching, freeze‐drying, air incorporation, emulsion templating, and thermally induced phase separation . Most of the studies, however, are hampered by disadvantages in terms of the pore size control and the multistep fabrication procedure.…”
Section: Introductionmentioning
confidence: 99%